Antibody responses among adolescent females receiving the quadrivalent HPV vaccine series corresponding to standard or non-standard dosing intervals. Issue 16 (15th April 2015) - Russell, Kate; Dunne, Eileen F.; Kemper, Alex R.; Dolor, Rowena J.; Unger, Elizabeth. R.; Panicker, Gitika; Markowitz, Lauri E.; Walter, Emmanuel B.
Abstract: Quadrivalent human papillomavirus vaccine (HPV4) is recommended as a 3-dose series administered at 0, 1–2, and 6 months. However, this dosing schedule is often not followed leading to longer dosing intervals. We conducted a prospective study to assess antibody titers to HPV4 when dose 2 and/or dose 3 were administered on schedule or delayed. Healthy females ( N = 331) aged 9–18 years were enrolled at the time of receipt of HPV4 dose 2 or 3. Participants were classified as belonging to one of four groups depending upon timing of receipt of HPV4: both doses on time; only dose 2 delayed later than 90 days; only dose 3 delayed later than 180 days; or both doses 2 and 3 delayed. Pre- and post-dose 3 blood samples were assayed for HPV antibody titers (types 6, 11, 16, and 18). Post-dose 3 geometric mean titers (GMTs) for all HPV types were not significantly lower for any of the delayed dosing groups when compared to the on time group. When compared to the on time group, the post dose 3 GMTs in the delayed dose 3 group were significantly higher ( p < 0.05) for HPV types 6, 11, and 16. Our findings suggest that delays of dose 2 or 3 do not interfere with immune responses after completion of the 3-dose series. These results support current recommendations to not administer additional doses of HPV4 vaccine if dose 2, dose 3, or both doses have been administered late.